2021
DOI: 10.3390/cancers13020343
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein La Mediates TGFβ-Induced Epithelial to Mesenchymal Transition and Cancer Stem Cell Properties

Abstract: Background: the aberrant overexpression of predominantly nuclear localizing RNA-binding protein (RBP) La contributes to proliferation, mobility, and chemoresistance of cancer cells and tumor growth in mice. Methods: studies included cancer tissue microarrays (TMAs) analyses, cancer tissue data mining, transforming growth factor β (TGFβ)-induced cancer cell plasticity studies, three dimensional sphere growth, epithelial to mesenchymal transition (EMT) assays, analysis of cancer stem cell (CSC) marker expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The cells change to a spindle-shaped mesenchymal morphology and express markers associated with the mesenchymal cell state, such as N-cadherin, Vimentin, and fibronectin [ 42 , 43 ]. Previous studies have shown that the gene SSB is associated with EMT, and the motility and invasion ability of squamous cell carcinoma cells are decreased after knockdown of SSB, and the expression of matrix metalloproteinase 2 (MMP-2) protein is significantly decreased [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells change to a spindle-shaped mesenchymal morphology and express markers associated with the mesenchymal cell state, such as N-cadherin, Vimentin, and fibronectin [ 42 , 43 ]. Previous studies have shown that the gene SSB is associated with EMT, and the motility and invasion ability of squamous cell carcinoma cells are decreased after knockdown of SSB, and the expression of matrix metalloproteinase 2 (MMP-2) protein is significantly decreased [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specific information is as follows: sh-scramble (5 ′ -TGTGAGGAA CTTGAGATCT-3 ′ ), sh-SSB1 (5 ′ -CCTGCATCCAAACA ACAGAAA-3 ′ ) and sh-SSB2 (5 ′ -GCTGAAATGAAATCTC TAGAA-3 ′ ). The shSSB base sequence is based on previously studied and verified sequence information [17].…”
Section: Transfection Of Hepatocarcinoma Cellmentioning
confidence: 99%
“…As such it is this small subset of cells that needs to be targeted in order to eradicate the tumor ( Bao et al, 2006 ; Dick 2008 ; Al-Assar et al, 2009 ; Mroz et al, 2013 ; Dionne et al, 2015 ; Subramanian et al, 2017 ; Zonga et al, 2018 ; Hu et al, 2019 ; Shibata and Hoque 2019 ; Keysar et al, 2020 ; Saito et al, 2021 ). More recently there has been an evolution in this model that suggests an inherent plasticity to CSCs that is mediated through the TME, arguing against the unidirectionality of the CSCs models ( Chaffer et al, 2013 ; Sancho et al, 2015 ; Shimokawa et al, 2017 ; Ahmed et al, 2018 ; Yao et al, 2019 ; Heise and Sommer 2021 ). This highlights the importance of a deeper understanding of the plasticity and interactions with the TME to identify new ways to target cancer stem cells to move the field forward.…”
Section: Introductionmentioning
confidence: 99%
“…La protein is highly expressed in various malignant tumors, and its expression is related to the clinical TNM stage, lymph node metastasis, and differentiation degree of tumor cells, which plays an important role in the translation control of tumor promoters ( 10 13 ). It can promote the tumorigenicity, change the cell cycle, and promote the proliferation, migration, and invasion of cancer cells ( 12 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can also promote the translation of Bcl-2, which may promote drug resistance by inhibiting the apoptosis of cancer cells. La protein mediates transforming growth factor β (TGF β)-induced epithelial–mesenchymal transition and cancer stem cell characteristics, contributing to the proliferation, migration, chemoresistance, and tumor growth of mouse cancer cells ( 10 ). It is an essential component of the X-linked inhibitor of apoptosis protein (XIAP) IRES ribonucleoprotein complex.…”
Section: Introductionmentioning
confidence: 99%